C‐Kit SCF receptor (CD117) expression and KIT gene mutation in conjunctival pigmented lesions. (7th June 2013) - Alessandrini, Lara; Parrozzani, Raffaele; Bertorelle, Roberta; Valentini, Elisa; Candiotto, Cinzia; Giacomelli, Luciano; Midena, Edoardo; Blandamura, Stella
Abstract. Purpose: To investigate the presence of KIT gene mutations and immunoreactivity in 85 conjunctival melanocytic tumours and to clarify the role of KIT as a potential therapeutic target in this group of patients. Methods: Eighty‐five conjunctival pigmented tumours [27 melanomas, 12 primary acquired melanosis (PAMs) and 46 nevi] were immunostained for KIT. Intensity and pattern of expression were evaluated. Molecular analysis to identify KIT mutations was performed in 15 selected cases (tumour‐rich areas >50%). KIT immunostaining score and pattern were statistically related to patients' age, sex, diagnostic category, presence of relapse, disease‐free survival, presence of metastases, metastasis‐free survival, limbal versus nonlimbal tumour location and thickness of melanomas. Results: KIT stains were documented in 48% of melanomas, 50% of PAMs and 24% of nevi. The mean score of KIT staining in the melanomas/PAMs group was significantly different from nevi (p = 0.0076). No statistically significant differences were detected between either c‐kit immunostaining score or pattern and each of the other clinico‐pathologic parameters considered. No KIT gene mutations were detected in melanomas and nevi. A silent mutation/polymorphism in KIT exon 13 was found in one PAM. Conclusions: Despite the high level of KIT immunostains in PAMs and melanomas, this parameter seems not to be a good predictor of the presence of molecular mutations. KIT‐activating mutations should be considered an uncommon event in this tumour.